Design of Event Management Application for ITU-UUM - Omar, Hamed F. Hamed (2010)
Organizing events is a problem that concerns every teaching institution. Every year new events must be produced to take account of staff, student causing a necessarily large amount of work in ITU- UUM. The objective of this study was to create an event management system for ITU-UUM. As many events are organized. Nowadays, there is a need for an application in order to help organizing all the events effectively. Beside, the research methodology used in this study was an agreeable method and Significance which has been used by several scholars in this field. Implementing this prototype at UUM will return in many benefits for both staff and the students. However some work and studies still need to be done to this system as described in the recommendations section.